Psychiatric genetic counseling for people with copy number variants associated with psychiatric conditions. Issue 5 (7th September 2022) - Morris, Emily; Inglis, Angela; Austin, Jehannine
Abstract: 22q11.2 deletion is one of the most well‐known copy number variants (CNVs) associated with developing a psychiatric condition (e.g., schizophrenia), but there is a growing list of other CNVs which also confer substantial risk for developing psychiatric conditions. With increased use of chromosome microarray and exome sequencing, the frequency with which these CNVs are detected is increasing. While individuals with such CNVs often receive genetic counseling, research shows that associated psychiatric conditions are less often addressed—clinicians tend to focus on the nonpsychiatric manifestations of the CNV. This represents an important service gap for people with these CNVs and their families, as research shows that not only do these families want genetic counseling about psychiatric illness, it can also produce meaningful positive outcomes for people, including increases in empowerment, and self‐efficacy. Therefore, there is a need to ensure that individuals with psychiatric condition‐associated CNVs are being counseled about these manifestations of their condition in a way that can promote the best outcomes. In this paper we describe the process of providing genetic counseling in two clinical scenarios in which a psychiatric susceptibility CNV is identified: (1) in an individual who has not been diagnosed with a psychiatric condition and (2) in an individual with an established psychiatric condition. Abstract : The jar model can be used to represent the way mental illness results from a combination of both genetic factors (e.g., a large‐effect CNV can be depicted with a large ball, and other genetic factors as small balls), and environmental factors accumulating to produce illness. Adapted by Ben Austin from "How to talk with families about genetics and psychiatric illness". Copyright (c) 2011 by Holly Peay and Jehannine Austin. Used with permission of the publisher, W.W. Norton & Company, Inc. All rights reserved